Curcumin Supplementation Protects Broiler Chickens Against the Renal Oxidative Stress Induced by the Dietary Exposure to Low Levels of Aflatoxin B1 - Damiano, Sara; Jarriyawattanachaikul, Watanya; Girolami, Flavia; Longobardi, Consiglia; Nebbia, Carlo; Andretta, Emanuela; Lauritano, Chiara; Dabbou, Sihem; Avantaggiato, Giuseppina; Schiavone, Achille; Badino, Paola; Ciarcia, Roberto (Frontiers in Veterinary Science, 2022)
Aflatoxin B1 (AFB1) causes hepatotoxicity, immunotoxicity and kidney damage, and it is included in group I of human carcinogens. The European Commission has established maximum limits of AFB1 in feed, ranging from 5 to 20 μg/kg. Chicken is moderately sensitive to AFB1, which results in reduced growth performance and economic losses. Oxidative stress triggered by AFB1 plays a crucial role in kidney damage and the antioxidant activity of curcumin (CURC) could help in preventing such adverse effect. Twenty-days-old broilers were treated for 10 days with AFB1 (0.02 mg/kg feed), alone or in combination with CURC (400 mg/kg feed), to explore the effects on the renal tissue. Animals exposed to AFB1 alone displayed alterations of the oxidative stress parameters compared with controls: serum antioxidant capacity, and enzymatic activity of kidney superoxide dismutase, catalase and glutathione peroxidase were decreased, while renal malondialdehyde levels and NADPH oxidase complex expression were increased. The administration of CURC attenuates all the oxidative stress parameters modified by AFB1 in the chicken kidney, opening new perspectives in the management of aflatoxicosis.